Legal Protection of Auction Winners Against the Execution of Dependent Rights - Octavian, Verri (Advances In Social Humanities Research, 2024)
According to Article 14 of the Law on Dependency Rights, dependency right enforcement can be executed through a parate of execution or a fiat execution by State courts. However, legal certainty is not absolute; if a debtor fails to repay the debt, the creditor's liability is settled by selling the secured object through a public auction. This study investigates the legal consequences of the auction process, particularly the transfer of auctioned property rights to the winner. Using empirical juris and analytical descriptive research, primary and secondary data were gathered through library research and qualitatively analyzed. Auction winners may request the local state court to vacate the object if possession is unattainable under the law. An auction letter, as an authentic act, protects auction winners against normative enforcement of dependency rights. Nonetheless, the law lacks explicit protection for third parties and auction winners regarding possession, resulting in legal uncertainty.